Self-Introspection as an Idea in Creating Paintings - Kepakisan, Gede Agung Nugraha Arya; Yudha, I Made Bendi; Kondra, I Wayan (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2024)
This thesis contains a description of the creation of works of painting with the theme